Gestão de informação: O caso das empresas participantes do programa de incubação de empresas daUniversidade Federal de Goiás - Gomes, Suely (2011)
The main objective of this paper is to point out the information management strategic profile of companies participating in the program of business incubation of Universidade Federal de Goiás (PROINE-UFG). This new alignment of social network aims to promote the competitiveness of micro and small business by approaching them to the knowledge producers that, in the Brazilian case, are the universities. The strategic information aligning model, proposed by Marchand, was used as the theoretical framework. The research took the design of a case study, as it limited to study the UFG incubation program. Nine companies of PROINE-UFG were investigated. The main conclusions are that the PROINE-UFG companies have a tendency of proactivity. Nevertheless the financial and technological resources are scarce to monitor the external environment as demanded by the strategy. They use few information sources and the interaction with the university is still incipient